Consumer Trends and New Product Opportunities in the Food Sector - Grunert, Klaus G (Wageningen Academic Publishers, 2017)
This book traces consumer trends regarding healthiness, sustainability, authenticity, and convenience. It gives an introduction to current developments in farming, in food processing technology, and in retailing. It also explains how segmentation and consumer-led product development can lead to new food products in response to these trends.